KEBIJAKAN SINOPTIK PENERAPAN HUKUM ADAT DALAM PENYELENGGARAAN PEMERINTAHAN DESA - Sutrisno Purwohadi Mulyono (Faculty of Law, Universitas Sebelas Maret, 2014)
AbstractArticle 18B (2) of the Constitution 1945 normatively recognizes and respects the unities of society with customary law with its traditional rights. However, in the context of emerging empirical question which is based on a number of issues regarding the presence or absence of the role of customary law in the administration of the village administration. This article aims to identify and analyze the existence of the application of customary law through synoptic policy in the administration of the village administration as an effort to strengthen participatory democracy. Approach selected was socio-legal research with qualitative data analysis (qualitative research) that is descriptive. Techniques in collecting the data are interview, documentation and observation. The study concludes that the involvement of customary law, citizens feel partially responsible for the implementation of village governance system. But along with the development policy of national law customary law sometimes neglected. Recommendations of this study can be used as a basis for developing policies synoptic application of customary law in the administration of the village administration.Keywords: Synoptic Policy, Village Government.AbstrakPasal 18B ayat (2) UUD 1945 secara normatif mengakui dan menghormati kesatuan-kesatuan masyarakat hukum adat beserta hak-hak tradisionalnya. Namun dalam konteks empiris muncul sejumlah pertanyaan yang bersumber pada permasalahan perihal ada tidaknya peran hukum adat dalam penyelenggaraan pemerintahan desa tersebut. Artikel ini bertujuan untuk mengetahui dan menganalisis eksistensi penerapan hukum adat melalui kebijakan sinoptik dalam penyelenggaraan pemerintahan desa sebagai upaya imemperkuat demokrasi partisipatoris. Pendekatan socio-legal research dipilih dalam penelitian kebijakan hukum ini menggunakan analisis data kualitatif (qualitative research) yang bersifat deskriptif. Teknik pengumpulan data dengan metode wawancara, dokumentasi dan observasi. Hasil penelitian menyimpulkan, dengan berperannya hukum adat, warga masyarakat merasa ikut bertanggungjawab terhadap terselenggaranya sistem pemerintahan Desa. Namun seiring dengan kebijakan pembangunan hukum nasional terkadang hukum adat terabaikan. Rekomendasi penelitian ini dapat digunakan sebagai dasar membangun kebijakan sinoptik penerapan hukum adat dalam penyelenggaraan pemerintahan desa.Kata Kunci : Kebijakan Sinoptik, Pemerintahan Desa.